Breaking Bad - Sharrett, Christopher (Book collections on Project MUSE., 2021)
Breaking Bad (2008-2013), a remarkable synthesis of the crime film, the sitcom, the western, and the family melodrama, is a foundational example of new television in the early twenty-first century. Receiving multiple Emmy Awards, it launched the careers of its creators and stars, most notably Bryan Cranston as high school teacher turned drug manufacturer Walter White, whose attempt to grab the American dream results in the destruction of family, home, community, and himself. In this book, Christopher Sharrett examines the innovations of Breaking Bad through a study of its main character, using psychoanalysis, genre study, gender studies, American studies, and the graphic arts to assist an exploration of the supreme danger of modern, postindustrial toxic masculinity embodied in Walter White. Serving as a fresh start for the American Movie Classics (AMC) cable outlet, Breaking Bad is probably the most uncompromised rendering of the white American male's rage in early twenty-first-century fiction. Set against a deindustrialized American landscape, its conflicted morality can seem less ambiguous than repugnant when we note the use of humor throughout, particularly as characters are introduced and killed off. Walter's relationships with his son, who has cerebral palsy, his former student turned business partner, his long-suffering wife, and his DEA brother-in-law are layered on top of the show's reflection of the very real challenges facing America today, which are not limited to the opioid epidemic, lax gun laws, and racial violence. Some critics have accused Breaking Bad of inciting a disturbance rather than criticizing, as it relies heavily on the audience's humor. Sharrett's argument for why the show is the canniest dramatic insight of our times is worth the price of admission for scholars and students of media studies and superfans alike. analysis of the acclaimed TV series and its portrait of societal decline.